ДОСЛІДЖЕННЯ ДИНАМІКИ ФІНАНСУВАННЯ ПРОГРАМ ІМУНОПРОФІЛАКТИКИ В УКРАЇНІ - Федяк, І. О.; Іванюлик, І. І. (Фармацевтичний часопис, 2015)
Introduction. World Health Organization is worried about poor children vaccination inUkraine. After the signing of the coalition agreement between the main political parties, which were held into the Ukrainian Parliament of VII convocation, representatives of WHO and UNICEF welcomed «the inclusion of conditions of vaccines procurement together with international partners and organizations in the coalition agreement, and reaffirmed their willingness to purchase and contribute in response to corresponding request of the Ministry of Health care of Ukraine». However, coordinated decisions were not accepted. And the overall condition of financing the health care system and the Program of immunization as its component does not comply with the WHO’s requirements. Methods of research: bibliographical, analytical, systematic and logical. Results and discussion. According to the immunization Schedule in Ukraine, 10 infectious diseases, such as diphtheria, pertussis, rubeola, rubella, epidemic parotitis, polio, tetanus, tuberculosis, hemophilic infection, hepatitis B are subordinated to prevention by vaccination. Vaccines against these diseases in accordance with the law of Ukraine № 1645-14 «On protection of population against infectious diseases» are centrally purchased on a single state tender held by the Ministry of Health care of Ukraine. Nowadays, it is currently completing the implementation of current National program of immunization and population protection against infectious diseases for 2009-2015, which was adopted by the Law of Ukraine № 1658-VI, dated on 21st October, 2009. The problem of infectious diseases immunization must be strategic in any socio-political circumstances of country’s life. However, according to analysis of the state funding of the health care system ofUkraineas in general and as its component – system of immunization inUkrainetraditionally faced a shortage of funds, along with the low cost effectiveness. This tendency has occurred not only in the current military conflict, but also has become a disappointing practice. So, the percentage of financing costs on the health care system from the State budget has traditionally been at the level of 3,7% of GDP and covers about 57% of the total population needs. However, the analysis of audits materials of the Accounting chamber of Ukraine shows that projected amount of funding from the State budget of the Program on immunization during 2009-2015 variances with the real allocations in 2011-2013 inaverage of 45,3%. Along with this, the conclusions of the Accounting chamber for 2007-2013, Ministry of health care traditionally does not provide efficient use of available funds of the State budget. This led to the fact that it was failed to reduce the level of infections, against which is held by means of immunization. This is demonstrated by the vaccination coverage of the population in 2014 at a level from 15 to 49% depending on infectious disease by the WHO recommendations – 95 %. Conclusions: reform of the Program of immunization financing must firstly focus on improving the efficiency of spending, particularly through the reform of sector procurement that is offered like in many countries to conduct through the mediation of WHO and UNICEF through the «framework» (directly long-term) agreements with suppliers of vaccines. And it already needs not declarative, but real political freedom.